2016
DOI: 10.3390/w8110536
|View full text |Cite
|
Sign up to set email alerts
|

Acid Water Neutralization Using Microbial Fuel Cells: An Alternative for Acid Mine Drainage Treatment

Abstract: Acid mine drainage (AMD) is a complex environmental problem, which has adverse effects on surface and ground waters due to low pH, high toxic metals, and dissolved salts. New bioremediation approach based on microbial fuel cells (MFC) can be a novel and sustainable alternative for AMD treatment. We studied the potential of MFC for acidic synthetic water treatment through pH neutralization in batch-mode and continuous-flow operation. We observed a marked pH increase, from~3.7 to~7.9 under batch conditions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Acid mine drainage (AMD) is a major problem all over the world. AMD is produced when sulfide-bearing material, from mine sites or natural sources, is exposed to water and oxygen [1,2]. The main problem caused by AMD is pollution due to low pH, high concentrations of dissolved metals (i.e., iron, aluminum, copper, lead, zinc and silver, among others), metalloids (e.g., arsenic) and sulfate [3].…”
Section: Introductionmentioning
confidence: 99%
“…Acid mine drainage (AMD) is a major problem all over the world. AMD is produced when sulfide-bearing material, from mine sites or natural sources, is exposed to water and oxygen [1,2]. The main problem caused by AMD is pollution due to low pH, high concentrations of dissolved metals (i.e., iron, aluminum, copper, lead, zinc and silver, among others), metalloids (e.g., arsenic) and sulfate [3].…”
Section: Introductionmentioning
confidence: 99%
“…SRB grow optimally under circum-neutral conditions, therefore the AMD treatment that is mediated by SRB requires pH neutralization. However, many researchers have studied acid-tolerant and acidophilic SRB [21,[36][37][38][39][40]. Kimura, et al [41] have reported a reduction of sulfate at pH 3.8, and Bijmans, et al [42] reported a high rate of sulfate reduction at pH 4.0 and 4.5 using H 2 and formate as electron donors in laboratory experiments.…”
Section: Metal-tolerant Sulfate Reducing Bacteria Are Tolerant To Low Phmentioning
confidence: 99%
“…Several approaches for heavy metal removal have been employed, such as ion exchange, precipitation, reverse osmosis, adsorption, membrane separation, bioremediation and phytoremediation [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Likewise, the removal of metallic pollutants and the degradation of persistent organic pollutants has also been explored by different technologies based on photocatalyst applications [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%